Adsorption process of tetrachloroethylene (PCE) on network growth ring. Issue 6 (7th March 2020) - Huang, Wanyi; Zhong, Dan; Yuan, Yixing; Ma, Wencheng; Yuan, Yuan; Liu, Bohan
ABSTRACT: This study was undergone to investigate the adsorption characteristics of tetrachloroethylene (PCE) on water supply network growth ring. According to the chemical composition of real network growth ring, iron oxide mixture containing synthesized goethite and lepidocrocite was applied as simulated growth ring. The results demonstrate that competition could take place only between PCE and the co-present organic non-ionic compound, while inorganic salt had no discernible effect on PCE adsorption. A maximum adsorption capacity of 33.118 mg g −1 at equilibrium was achieved. By the non-linear regression method, the equilibrium adsorption data fitted well with the Freundlich isotherm model (R 2  = 0.994), and the kinetic data obeyed pseudo-first order model (R 2  = 0.985). Thermodynamic tests indicate the spontaneous and exothermic nature of adsorption process. In addition, no significant variation between the FTIR spectra of the iron oxide mixture before and after adsorption was observed, which verifies that hydrogen bonds between PCE and mineral mixture could be neglected. An overview of the experimental results leads to the conclusion that the adsorption of PCE onto the simulate growth ring was driven by dispersion and hydrophobic interactions. As a case study, this work will provide some information about water supply securit protection. GRAPHICAL ABSTRACT: